2013
DOI: 10.1371/journal.pone.0082431
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Influenza A Virus Matrix Protein M1 and Its Self-Assemblies at Low pH

Abstract: Influenza A virus matrix protein M1 is one of the most important and abundant proteins in the virus particles broadly involved in essential processes of the viral life cycle. The absence of high-resolution data on the full-length M1 makes the structural investigation of the intact protein particularly important. We employed synchrotron small-angle X-ray scattering (SAXS), analytical ultracentrifugation and atomic force microscopy (AFM) to study the structure of M1 at acidic pH. The low-resolution structural mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 45 publications
26
51
0
2
Order By: Relevance
“…These results suggest that ML should be a structurally polarized molecule with a stable Nterminal domain (MN) and a C-terminal domain available for proteolytic attack. The result is consistent with the previous reports about IAV M1 (Shishkov et al, 2011;Shtykova et al, 2013). Therefore, MN was further studied using X-ray crystallography method (Fig.…”
Section: Conformational Changes Between the Neutral And Acidic Thov Msupporting
confidence: 91%
“…These results suggest that ML should be a structurally polarized molecule with a stable Nterminal domain (MN) and a C-terminal domain available for proteolytic attack. The result is consistent with the previous reports about IAV M1 (Shishkov et al, 2011;Shtykova et al, 2013). Therefore, MN was further studied using X-ray crystallography method (Fig.…”
Section: Conformational Changes Between the Neutral And Acidic Thov Msupporting
confidence: 91%
“…Our small-angle X-ray scattering experiments (18) proved that M1 is also a monomer at pH 4.7 with a small tendency to form helical oligomers but not dimers. While the C-terminal domain is most likely responsible for the interaction of M1 with viral RNP (5), there is also a possible role for this domain in protein dimerization (19).…”
mentioning
confidence: 52%
“…The deviation from equation 3 after 110 nM M1 is due not to second-layer completion (see further AFM experiments) but probably to the anisotropy of the M1 molecule (18): the C-terminal domain is responsible for M1-RNP binding, while the N-terminal domain presumably interacts with the lipid bilayer (5). Thus, different protein-protein interactions reign within the first and the second layers versus between the layers.…”
Section: M1 Adsorption At Neutral Phmentioning
confidence: 99%
“…Similarly, studies on FLUC-M1 also showed that membrane tubule formation requires its C domain, corroborating its essential role for FLUC-M1 polymerization (22). In vivo, the 2D M1 lattice formation is likely promoted by cell membrane, as it has been shown that FLUA-M1 and FLUC-M1 oligomer formation is strongly enhanced by membrane binding and does not require the presence of other viral proteins (22,41).…”
Section: Resultsmentioning
confidence: 63%
“…The requirement of both N and C domains for 2D lattice formation likely explains why similar 2D lattices have not been observed in the crystal structures of FLUA-M1, FLUC-M1, and THOG-M1 that only include the N domain. An earlier study using small angle X-ray scattering indicated that the full-length FLUA-M1 monomers coexist in solution with a small fraction of large clusters with a layered architecture (41), suggesting a key role of the C terminus of FLUA-M1 in the formation of 2D lattice sheets. Similarly, studies on FLUC-M1 also showed that membrane tubule formation requires its C domain, corroborating its essential role for FLUC-M1 polymerization (22).…”
Section: Resultsmentioning
confidence: 98%